KAJIAN YURIDIS PEMAKAIAN REKAM MEDIS ELEKTRONIK DI RUMAH SAKIT - Cinthia Mutiara Hapsari; Ary Subiyantoro (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2019)
Backgroud: A hospital was a part of a whole system health services which aims to carry out health services, these services through the effort to healing patients .In order to to support these health services then required health information of the members of the data that is neither of the patients medical record. Objective:to determine the usage of electronic medical record in hospital. Method:The method used in this research was normative yuridis.  The data presented in the form of the patient medical record manually and electronic medical record , and the data it is very important to the hospital .Because of that , needed  there is research on how the comparison between medical record manuals by electronic medical record if record of profit and weaknesses and how in terms of safety data storage electronic medical record compared to manual medical record and assess whether electronic medical record can be used as an instrument the evidence in the investigation in the provision of health services related to not repeat this research with methods of juridical normative. Result: This research gained an electronic medical record. The results showed that has certain excellence that more so than with manual medical .Medical can also record it becomes a tool the evidence in the investigation in a similar way manual medical record. Conclusion: The conclusion of this research was the usage of electronic medical record is more savety, accurate and effective in hospital